HUBUNGAN ANTARA KEBIASAAN BELAJAR DENGAN HASIL BELAJAR SISWA KELAS IV DI SD NEGERI 101928 RANTAU PANJANG KECAMATAN PANTAI LABU TAHUN AJARAN 2020/2021 - Ali Imron; Wahyu Hidayat Hidayat (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2021)
This research is a quantitative research with correlation method. The population in this study were fourth grade students at SD Negeri 101928 Rantau Panjang, Pantai Labu District, for the 2020/2021 academic year, totaling 265 with a sample of 80 students. The sampling technique was carried out by means of quota sampling. Data collection techniques in this study were observation, unstructured interviews, questionnaires, and documentation which were analyzed using descriptive statistical analysis. Prerequisite analysis test includes data normality test and regression linearity test. Hypothesis testing includes Product Moment correlation test, and the coefficient of determination. The results showed that: (1) the study habits of fourth grade students with a percentage of 38.75% were classified as moderate; (2) student learning outcomes with a percentage of 36.25% are quite sufficient; (3) there is a significant relationship between study habits and learning outcomes of 31% indicated by the presence of tcount > t table (0.559> 0.220) and a significance level of 0.05, the correlation in this study is moderate. The conclusion of this research is that there is a significant relationship between study habits and learning outcomes, and it is classified as moderate. Suggestions teachers should pay attention to and monitor student learning outcomes by providing guidance and motivation to be more enthusiastic in learning and students can get used to learning optimally.